Świat bogów i ludzi w średniowiecznych poematach bengalskich - Grabowska, Barbara (Gajt Wydawnictwo 1991 s.c., 2018)
The article discusses the process of readjustment of the Bengal native gods’ cults – containing elements inconsistent with brahmin culture – to the images of the gods known from the Great Tradition. The readjustment consisted of taking over known gods’ names and bynames, introduction of classical themes from poetry, epic poems and Puranas to old tribal myths, praising the power, glory and deeds of native gods as well as describing the favours granted to their worshippers. The meaning and the role of the Puranic gods were decreased while Śiva and his family came to power. As a result old rural and tribal gods began receiving puja type sacrifice – just like the great gods; every now and then even a sacrifice made by a brahmin is mentioned.
Keywords: mangal; Bengali literature; Bengali native gods; Bengali tribal myths; GreatTradition